Peningkatan Pemahaman Terhadap Penggunaan Manajemen Reference Dalam Penulisan Skripsi Pada Mahasiswa Pascasarjana UIN Padangsidempuan - Edriagus Saputra; Ammi Thoibah Nst; Anita Adinda; Rina Sari Lubis; Asrin Nasution; Suparni Suparni; Muhammad Zia Alghar (Jurnal Pengabdian Masyarakat, 2026)
Problems in academic writing among postgraduate students are still frequently found, particularly related to inaccurate citations, inconsistent bibliographies, and limited use of reference management applications. This community service program aimed to improve postgraduate students’ understanding and skills in using reference management applications to support systematic and academically appropriate scientific writing at UIN Syekh Ali Hasan Ahmad Addari Padangsidimpuan. The program was conducted through training sessions and hands-on practice using Zotero and Mendeley applications involving 65 participants, consisting of 45 students from the Primary Education Study Program and 20 students from the Mathematics Education Study Program. Program evaluation was carried out through observation and post-training questionnaires. The results showed that 42 participants (65%) rated the quality of material delivery as very good, while 43 participants (66%) reported a very high level of understanding regarding the use of reference management applications. Participants were also able to install the applications, manage references, and apply automatic and manual citation techniques correctly. The program proved effective in improving students’ academic literacy and reference management skills, thereby supporting the enhancement of scientific writing quality and strengthening an orderly and integrity-based academic culture.